2020
DOI: 10.1016/j.bjoms.2020.06.038
|View full text |Cite
|
Sign up to set email alerts
|

What are the limitations of the non-patient-specific implant in titanium reconstruction of the orbit?

Abstract: There is ongoing discussion about patient-specific implants (PSI) to reconstruct orbital defects. Although PSI offer excellent clinical outcome, they are expensive. Subsequently, their routine application is not indicated. The purpose of this study was to estimate the frequency of implant malposition and revision procedures after primary orbital repair with preformed plates and to identify cases where primary use of PSI would help to prevent revision surgery. All patients included in the study were operated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 15 publications
(25 reference statements)
0
29
0
3
Order By: Relevance
“…A tentative conclusion may be that not every inaccuracy in implant position will lead to an adverse clinical outcome, but if revision is required, there is a high chance that the implant was malpositioned in the previous reconstruction. Remarkably, Schlittler et al identified the same main reason for revision as can be concluded from Table 3: treating a defect with a mesh that is too small 45 . This can easily be avoided if preoperative surgical planning is conducted.…”
Section: Discussionmentioning
confidence: 81%
“…A tentative conclusion may be that not every inaccuracy in implant position will lead to an adverse clinical outcome, but if revision is required, there is a high chance that the implant was malpositioned in the previous reconstruction. Remarkably, Schlittler et al identified the same main reason for revision as can be concluded from Table 3: treating a defect with a mesh that is too small 45 . This can easily be avoided if preoperative surgical planning is conducted.…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, in this case, we found an advantage in the use of the PSI, which, in addition to providing a more anatomical reconstruction, does not present irregular surfaces, edges or protrusions of the osteosynthesis material that could compromise the reconstruction or the patient’s comfort. [ 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Результати. Середня різниця об'єму між інтактною та неушкодженою орбітою до оперативного втручання становила 3,4 ± 2,5 в основній групі та 2,8±1,1 в контрольній (р>0,05), після операції -0,68±0,28 cм 3 та 0,71±0,21cм 3 (р>0,05). Безпосередньо перед хірургічним етапом лікування частка посттравматичного енофтальму в основній групі становила 70,1%, а в контрольній -74,1%, тоді як у віддаленому післяопераційному періоді жодного випадку залишкового енофтальму виявлено не було.…”
Section: реконструкція орбіти на основі цифрового моделювання: оцінка ефективності автоматизованих систем сегментаціїunclassified
“…Середня тривалість етапу комп'ютерного моделювання в основній групі була 36,7±6,9 хвилин проти 72,9±7,7 хвилин в контролі (p<0,001). В основній групі оперативне втручання в середньому тривало 57,5±14,7 хвилин, тоді як у контрольній групі -58.3±11, 3 Результати та їх обговорення. Порівняльний аналіз результатів лікування виявив, що середня різниця об'єму між інтактною та неушкодженою орбітою до оперативного втручання становила 3,4 ± 2,5 в основній групі та 2,8±1,1 -в контрольній (р>0,05), після операції цей показник відповідно склав 0,68±0,28 cм 3 та 0,71±0,21cм 3 (р>0,05).…”
Section: реконструкція орбіти на основі цифрового моделювання: оцінка ефективності автоматизованих систем сегментаціїunclassified
See 1 more Smart Citation